Identifikasi Perilaku Perataan Laba Melalui Berbagai Konsep Laba - Mursalim Mursalim (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2010)
The objective of the paper is to identify income smoothing by the four income concepts: operating income, income from operations, income before extraordinary items and net income. This research using research sample of 151 the manufacture company registered in Indonesia Stock Exchange during the years of 1999-2007. The samples determined by using a purposive sampling method.The research results shows that 58 (38,41%) the firm identified as an income smoother by operating income and 69 (45,70%) the firm identified as an income smoother by income from operations and 67 (44,37) by income before extraordinary items. Further results show that 47 (31,13%) the firm identified as an income smoother by net income and 24 (15,89%) the firm identified as an income smoother by the four income approach simultaneously; operating income, income from operations, income before extraordinary items and net income. Finally, this study shows that 95 (62,91%) the firm identified as an income smoother during the research period.Keywords: income smoothing, operating income, income from operations, income before extraordinary items dan net income